FLOWERING PLANTS USED IN LANDSCAPING WORK (British Journal of Global Ecology and Sustainable Development, 2022)
This article, written on” flowering plants used in landscaping work", tells about the number of species on Earth and listed in the Red Book of plants from the most showy species of flowering plants, scientific work on flowers used in landscaping work and conducted practical experiments on them, professor R.H.Eyupav or.X. Reviews of yuldashovs and some bulbous plants about the technologies of their cultivation, the classification of tulip flower varieties about different types of flowers, the methods of their protection from diseases and pests are given. Information about the floriculture companies and contacts carried out in this area is provided in our republic.